Exchange rate intervention in small open economies. Bayesian estimation of a DSGE model for Iceland - Steinar Björnsson 1984- (2010)
In this thesis the welfare effects of exchange rate intervention in small open economies will be examined. A dynamic stochastic general equilibrium model is built that incorporates the basic features of these economies. A monetary policy that responds to the inflation rate and the output gap is compared to monetary policies that additionally respond to the real exchange rate. The reaction of the economy to various shocks is examined and the welfare loss is estimated in order to compare monetary policies. Historical observations of various parameters for the Icelandic economy are used to estimate the parameters of the model using Bayesian estimation. This thesis shows that in order to reduce the welfare loss introduced by various exogenous shocks exchange rate intervention is necessary. Exchange rate intervention reduces the observed volatility in the output gap, the domestic inflation and in the interest rate when used in response to certain exogenous shocks. Keywords: DSGE model, Bayesian estimation, Iceland, Icelandic economy, exchange rate intervention, monetary policy, small open economy, dynamic stochastic, general equilibrium, exchange rate, interest rate.